On the inscription on the baptismal font from the time of Prince Višeslav: Some epigraphic remarks - Komatina Predrag (Zbornik Radova Vizantološkog Instituta, 2022)
The paper discusses some epigraphic features of the inscription on the baptismal font of the priest John from the time of Prince Višeslav from the end of the 8th and the beginning of the 9th century and points out the similarities and parallels between it and the inscription of Bishop John of Kotor on the architrave in the Kotor Cathedral of St. Tryphon from 805. Based on them, it is assumed that the baptismal font could also be attributed to the famous “Kotor stonecarvers’ workshop from the time of Bishop John”.